Universidades públicas: das contribuições do conhecimento na Pós-Graduação ao desenvolvimento regional - SILVA, Keila Paiva da (Universidade Federal do Pará, 2012)
This study presents an analysis on the contribution of the knowledge acquired in graduate school for Regional Development, grounding into two streams: one that defends the traditional idea of investment in basic science as an essential element for economic development of any region and one that supports the interdisciplinary response to the fragmentation caused by a positivist epistemology of nature that has been occupying more space in Brazilian universities with the increasing expansion of post-graduate studies before the need for the knowledge society, informational and globalized, modern science will impose as a solution to this new organizational form. The research was based on secondary data collection and these were analyzed using correlation coefficients, specialization and restructuring. The results of these regions showed that despite being in development, regional inequality still limits the innovation process in the country, this being one of the factors that prevent equitable economic growth of regions.